PotensiEkstrakKulitPisang (Musa Paradisiaca) SebagaiAntibakteri Ralstonia solanacearum Penyebab Penyakit Layu Bakteri Tanaman Tomat - Isroni, Muhson; Paskariani, Angela Enggar; Setiawan, Fauzi Fandy; Rakhmawati, Anna (Universitas Sebelas Maret, 2018)
Indonesia is one of the largest banana-producing countries in the world. Unfortunately, the high demand for bananas has not been balanced with the utilization of banana peels well. Thus, the high production of banana indicates the high amount of banana peel waste produced. On the other hand, tomato production from year to year tends to decrease. According to the Director General of Holticulture (2015), tomato production in 2014 decreased by 76.793 tons. One of the causes is the attack of Ralstoniasolanacearum bacteria that causes bacterial wilt diseases of tomato plants. Vegetable pesticides can come from banana peels because they contain toxin compounds such as flavonooids, sapoin, tannins, etc. Flavonoids will form complex compounds with extracellular and dissolved proteins that can damage the cell membrane of bacteria and followed by the release of intracellular compounds. This study aims to know the process of banana peel extract (Musa paradisiaca) in suppressing the growth of Ralstoniasolanacearum bacteria, which is most effective for inhibiting the growth of Ralstoniasolanacearum bacteria, This research is aÂ experimental research. the experiment is antibacterial test of banana peel extract on Ralstoniasolanacearum bacteria growth. The design pattern of the study used a completely nested randomized design pattern. The research started with the extraction process with maceration, making of NA and NB media, followed by rejuvenation and suspension of bacteria. After that, making test solution, then test the antibacterial activity with kirby-bauer method and last data retrieval. The results of Antibacterial test results showed positive results can inhibit the growth of Ralstoniasolanacearum bacteria is evidenced by ANOVA of significan value less than 0.05. The Duncan test results show that 100% of Ammon banana is the best to be used for antibacterial. So that banana peel potency to be developed become agent of vegetable pesticide on tomato plant.